Deposition of vaporized species onto glassy fallout from a near-surface nuclear test. (15th March 2017) - Weisz, David G.; Jacobsen, Benjamin; Marks, Naomi E.; Knight, Kim B.; Isselhardt, Brett H.; Matzel, Jennifer E.; Weber, Peter K.; Prussin, Stan G.; Hutcheon, Ian D.
Abstract: In a near-surface nuclear explosion where the resultant fireball can interact with the surface, vaporized materials from the nuclear device can be incorporated into molten soil and other carrier materials from that surface. This mixed material becomes a source of glassy fallout upon quenching and is locally deposited. Fallout formation models have been proposed; however, the specific mechanisms and physical conditions by which soil and other carrier materials interact in the fireball, as well as the subsequent incorporation of device materials with carrier materials, are not well constrained. We observe a surface deposition layer preserved at interfaces where two aerodynamic fallout glasses agglomerated and fused, and characterized 11 such boundaries using spatial analyses to better understand the vaporization and condensation behavior of species in the fireball. Using nanoscale secondary ion mass spectrometry (NanoSIMS), we identify higher enrichments of uranium from the device ( 235 U/ 238 U ratio >7.5) in 8 of the interface layers. Major element analysis of the interfaces reveals the deposition layer to be enriched in Fe, Ca, Mg, Mn, and Na-bearing species and depleted in Ti and Al-bearing species. Most notably, the Fe and Ca-bearing species are enriched approximately 50% at the interface layer relative to the average concentrations measured within the fallout glasses, while Ti and Al-bearing species are depleted by approximately 20%. SiO2 is found to be relatively invariable across the samples and interfaces (∼3% standard deviation). The notable depletion of Al, a refractory oxide abundant in the soil, together with the enrichment of 235 U and Fe, suggests an anthropogenic source of the enriched species or an unexpected vaporization/condensation behavior. The presence of both refractory ( e.g., Ca and U) and volatile ( e.g., Na) species approximately co-located in most of the observed layers (within 1.5 μm) suggests a continuous condensation process may also be occurring. These fallout formation processes deviate from historical models of fallout formation, and have not been previously recognized in the literature.